2014
DOI: 10.1128/jb.02418-14
|View full text |Cite
|
Sign up to set email alerts
|

The EcoKI Type I Restriction-Modification System in Escherichia coli Affects but Is Not an Absolute Barrier for Conjugation

Abstract: The rapid evolution of bacteria is crucial to their survival and is caused by exchange, transfer, and uptake of DNA, among other things. Conjugation is one of the main mechanisms by which bacteria share their DNA, and it is thought to be controlled by varied bacterial immune systems. Contradictory results about restriction-modification systems based on phenotypic studies have been presented as reasons for a barrier to conjugation with and other means of uptake of exogenous DNA. In this study, we show that inac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 42 publications
2
43
0
1
Order By: Relevance
“…Type I R-M systems attack dsDNA and thus, are not expected to degrade ssDNA during bacterial conjugation. However, it has been reported that the EcoKI R-M system affects the uptake of DNA by conjugation [26] and, ArdC is not expressed until plasmid DNA is in dsDNA shape. Thus, Type I R-M system could be attacking late, once ArdC is generated from the dsDNA plasmid after DNA entrance and establishment in recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…Type I R-M systems attack dsDNA and thus, are not expected to degrade ssDNA during bacterial conjugation. However, it has been reported that the EcoKI R-M system affects the uptake of DNA by conjugation [26] and, ArdC is not expressed until plasmid DNA is in dsDNA shape. Thus, Type I R-M system could be attacking late, once ArdC is generated from the dsDNA plasmid after DNA entrance and establishment in recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…We identified restriction-modification as a likely mechanism contributing to discrimination in transfer, showing that recipients with inactivated RM receive R1 plasmid at higher rates from field isolates. Restriction was previously shown to limit plasmid conjugation rates with relatively low efficiency (Roer et al, 2015), likely because the first transconjugants that escaped restriction are then protected from further restriction when transferring to kin. RM systems are tremendously variable and mobile among E. coli isolates (Murray, 2002;Barcus et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The restriction to clone-mates of high transfer rates suggests that barriers to transfer are not simply a function of genetic similarity. One barrier could be variation in restrictionmodification (RM) systems, which can lead to decrease in transfer rates (Roer et al, 2015):…”
Section: Variation In Restriction-modification Systems As a Mechanismmentioning
confidence: 99%
“…The ability of these systems to restrict foreign DNA could allow them to limit genetic exchange between species, thus potentially driving the diversification of microbial populations (Erwin et al, 2008;Budroni et al, 2011). Studies have demonstrated that RM systems can limit conjugal transfer of plasmids (Roer et al, 2015), and that they can limit the size of recombinant DNA fragments that are obtained via natural transformation (Lin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%